2017
DOI: 10.1002/adhm.201770099
|View full text |Cite
|
Sign up to set email alerts
|

Biosensing: Graphene Field‐Effect Transistors for the Sensitive and Selective Detection of Escherichia coli Using Pyrene‐Tagged DNA Aptamer (Adv. Healthcare Mater. 19/2017)

Abstract: An aptamer modified graphene field‐effect transistor (G‐FET) based biosensor for electrical detection of E. coli is developed by King Wai Chiu Lai and co‐workers in article number https://doi.org/10.1002/adhm.201700736. The change of the carrier density in graphene due to the attachment of E. coli is correlated with the electrical response of the graphene biosensors. The electrical response is analyzed and optimized by tuning the gate voltage which affects the carrier mobility of graphene. The excellent sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The change in thickness of the functionalized graphene was measured at several different locations while single step is shown as a representative plot. The relative increase in height from bare graphene is ~2.5–3 nm and is consistent with earlier reports (Wang, et al, 2016; Wang et al, 2015; Wu et al, 2017). Some dots were also seen on the SiO 2 surface probably due to the nonspecific adsorption of linker or aptamers while the untreated SiO 2 surface was clean (see Figure 2a).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The change in thickness of the functionalized graphene was measured at several different locations while single step is shown as a representative plot. The relative increase in height from bare graphene is ~2.5–3 nm and is consistent with earlier reports (Wang, et al, 2016; Wang et al, 2015; Wu et al, 2017). Some dots were also seen on the SiO 2 surface probably due to the nonspecific adsorption of linker or aptamers while the untreated SiO 2 surface was clean (see Figure 2a).…”
Section: Resultssupporting
confidence: 92%
“…The non-zero value of V D is attributed to the surface potential associated with Pt wire and not due to doping from the fabrication process (Chen et al, 2013;Wang et al, 2015). The obtained average field effect mobilities for electrons and holes were μ n = 1230 cm 2 /V.s and μ h = 1040 cm 2 /V.s respectively, demonstrating the high quality of our process and CVD graphene (Kireev et al, 2017;Wu et al, 2017). However, we have seen variation in the values of the maximum resistance measured with devices made in different chips/batches which could be either due to the disorder in the graphene or contact resistance.…”
Section: G-fet Characterizationmentioning
confidence: 69%
“…Interfacing compounds were introduced to immobilize the bioprobe onto the GM surface, and various interfacial compounds, including diaminonaphthalene (DAN), 1‐pyrenebutyric acid N‐hydroxysuccinimide ester (PANHS), bis(2‐aminoethylene)perylene‐3,4,9,10‐tetracarboxyldiimide‐diacid (PDI) and bis(2‐aminoethylene)perylene‐3,4,9,10‐tetracarboxyldiimide‐diamine (PDA), participated in π stacking interactions between the aromatic ring backbone and graphene [9, 10, 19–22] . π‐π interactions are a type of noncovalent interaction; therefore, the interaction energy is lower than that of covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a field‐effect transistor (FET) of the biosensor platform was fabricated by using a microelectromechanical systems (MEMS), and many energies, such as the thermal energy, vacuum energy, physical energy, and sound energy, were required for the MEMS process. Therefore, the introduction of OICs onto the graphene surface progressed after the MEMS process ended [8–13] . The conjugation efficiency of OIC interfacial compounds onto graphene and the introduction efficiency of the bioprobe are limited owing to steric hinderance or the amount of the activated functional group [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the electrochemical response current versus serotonin concentration, a calibration curve was plotted, fitting with the Langmuir adsorption isotherm (Fig. 1d) [74]. The corresponding plot showed that the response was proportional to serotonin concentrations over a range of 10 fM to 10 nM.…”
Section: Detection Of Serotonin With the Fet-based Sensor Platformmentioning
confidence: 99%